Used of artificial intelligence for city branding: a design for smart tourism city - Ina Primasari (Jurnal Mantik, 2023)
The world of artificial intelligence is a necessity that continues to grow to this day. Its utilisation crosses disciplines and time dimensions that seem to be narrowing. The purpose of this study is to describe the possibility of using the world of artificial intelligence for city branding purposes, more specifically as a smart tourism city. The research method is a literature review with a qualitative perspective. The results of the study found that the construction of the use of artificial intelligence in the development of smart cities is very possible. City branding with artificial intelligence is integrated with the construction of smart cities. In the discourse of this study, tourism city branding is a necessity for accelerated development, especially the tourism sector.